KONSTRUKSI I`LAN AL-NIKAH DALAM FIQH PANCASILA (Telaah Pencatatan Perkawinan Perspektif Sad Al-Dzariah) - Moh Mujibur Rohman; M Mohsi (Ulumuna: Jurnal Studi Keilsman, 2017)
The law on marital registration has juridical consequences, that marriage registration is a necessity of continuing legal actions in the form of marriage. Munakahat Fiqh does not know the name of marriage registration. The existence of marriage registration legislation creates a gap (dispute / conflict) between the law of fiqh munakahat with statutory regulations. in fiqh there is no registration of marriage. It's just that, for the sake of benefit and to avoid things muḍarat, then Islam (fiqh) recommends the existence of i'l al-nikâḥ (announcing marriage) which is then manifested in the form of wedding celebrations (walîmah al-shursh). Marriage that is not recorded at the competent authority raises many conditions, so that marriage registration is considered as a preventive measure (prevention) from the government as sadd al-dharî'ah (blocking the road).